Health Promotion Model Not Smoking among Adolescents: A Path Analysis Evidence from Indonesia - Sujono Riyadi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Smoking behavior is a threat to public health. This study identified factors that influence non-smoking behavior among adolescents. The aim is to determine the effect of media exposure, knowledge of the dangers of smoking, social capital, access to cigarettes among adolescents by using Theory of Planned Behavior (TPB).This cross-sectional study was conducted in Kulon Progo Regency, Yogyakarta Province, Indonesia, in April - May 2018. The dependent variable is non-smoking behavior. Independent variables were intention to not smoke, attitude to smoking, knowledge of tobacco use, subjective norms of not smoking, control of perceived behaviors for not smoking, media exposure to cigarette advertising, access to cigarettes and social capital among teenagers. Data were collected by questionnaire and analyzed by path analysis carried out in Stata 13.This study resulted in an attitude towards not smoking (b = 1,15; 95% CI = 0,55 to 1,75; p< 0,001), subjective norm for not smoking (b = 1,56; 95% CI = 0,96 to 2,16; p <0,001), and perceived behavioral control for not smoking (b = 1,99; 95% CI = 1,39 to 2,60; p <0,001), which affects the intention of not smoking, and finally on non-smoking behavior. Exposure to tobacco advertising has an indirect impact on non-smoking behavior through attitudes toward non-smoking (b = -0,82; 95% CI = -1,28 to -0,37; p< 0,001) and the intention not to smoke. This exposure to cigarette advertising also has an indirect impact on non-smoking behavior through low knowledge about smoking (b = -0,45; 95% CI = -0,47 to -0,03; p = 0,037). Weak social capital has an indirect impact on non-smoking behavior through subjective norms of smoking (b = 0,64; 95% CI = 0,25 to 1,05; p = 0,001) and the intention not to smoke. Knowledge about tobacco smoking (poor) impact on perceived behavior control not to smoke (b = 1,59; 95% CI = 1,15 to 2,03; p <0,001) and influential to attitude positive toward no smoking (b = 1,60; 95% CI = 1,16 to 2,05; p <0,001).Health promotion model with Theory of Planned Behavior (TPB) can be used to explain not smoking behavior among adolescents.